The importance of the OHIP (Oral Health Impact Profile) in Dentistry - Rivera-Ramos, Enith Shirley (2020)
The quality of life related to oral health is a primary indicator of the health situation. Different oral conditions influence in general health; also, in the perception of people about their biological, interpersonal and emotional comfort. In this literature review, it’s exposed one of the most used questionnaires in the evaluation of the assessment of the quality of life linked to oral health, the Oral Health Impact Profile (OHIP) and its variants. In the initial part, the definition of concepts such as quality of life and its relation to oral health, related to the subject, are presented. After that the results of investigations about the OHIP and its diverse modalities are shown (OHIP-49, OHIP-14, COHIP-19, OHIP-EDENT and OHIP-AESTHETIC).